Analysis of the Effectiveness of Arytenoidectomy and Posterior Cordectomy with the Use of CFD Airflow Measurements in Patients with BVFP: A Retrospective Study - Marta Gamrot-Wrzoł; Magdalena Marków; Daniel Janecki; Bogusława Orecka; Krzysztof Warmuziński; Maciej Misiołek (Applied Bionics and Biomechanics)
Purpose. Bilateral vocal fold paralysis (BVFP) is a rare larynx disease manifested by dyspnea, which often requires surgical treatment. The aim of the study is to determine the effectiveness of unilateral arytenoidectomy with posterior cordectomy in the treatment of BVFP using the computational fluid dynamics (CFD) method. Methods. This study included 33 patients with BVFP who underwent unilateral laser arytenoidectomy with posterior cordectomy. Glottis area measurements and spirometry, as well as a self-assessment of respiratory efficiency were performed before the surgery and after the recovery period. Using the CFD method, computer models of the glottis were made. Then, changes in air pressure gradient and maximum air velocity at the level of glottis were calculated, and local fields of pressure and air velocities were obtained. Results. The values of glottal surface area (S), spirometry parameters (forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and peak expiratory flow (PEF)), inlet air velocity at the glottal level as well as patients self-assessment of respiratory efficiency turned out to be significantly higher after the operation. The values of maximum velocity at the glottal level, pressure gradient at the glottal level turned out to be significantly lower after the surgery. We observed that the greater the increase in glottal surface area, the greater the decrease in self-assessment scales (visual analogue scale (VAS) and Medical Research Council (MRC)). Increased levels of spirometry parameters after the surgery correlated with smaller decrease of PEF-dependent pressure gradient at the glottal level (PEFΔPCFD). Conclusion. Unilateral laser arytenoidectomy with posterior cordectomy is an effective method for the treatment of BVFP. CFD is a useful tool to determine and visualize the effectiveness of surgical treatment in BVFP.